No Mate, No Problem: Molecular Mechanisms Involved in Parthenogenesis in the Cosmopolitan Earthworm Aporrectodea trapezoides (Annelida, Clitellata) - Irene de Sosa; Marta Turon; Sergi Taboada; José Lorente‐Sorolla; Rosa Fernández; Natasha Tilikj; Alberto Piris; Marta Novo; Patricia Álvarez Campos; Ana Riesgo (Molecular Ecology, 2025)
Approximately, 40% of earthworm species can reproduce by parthenogenesis. This is the case for the cosmopolitan species, Aporrectodea trapezoides , although sexual forms have been described sporadically. We analyse the genotypes and microbiomes of 30 individuals from four localities where both forms appear in order to understand the evolutionary mechanisms related to parthenogenesis. In all sites, heterozygosity values were approximately 30% higher in parthenogenetic individuals. However, we detected a stronger genomic structuring due to reproduction than to the geographical setting only in the Algerian population, underpinned by 195 loci that were related to gametogenesis, symbiont‐like processes, and nitrate reduction. Similarly, statistical differences in the abundance of ZOTUs were only found between the Algerian sexual and parthenogenetic earthworms, with 754 ZOTUs that included the genus Romboutsia , which is involved in the production of nitric oxide, which enhances sperm motility. In summary, significant genomic and microbiome differences were found only between sexual and parthenogenetic lineages in a single locality. We hypothesise that obligate parthenogenesis evolved early, leaving traces at the genomic and microbiome levels in the Algerian parthenogens that were the earliest splitting lineage. Such obligate parthenogenesis was lost secondarily and individuals in the Iberian sites were facultative parthenogens, with the potential to copulate and therefore erase the genomic and microbial traces of obligate parthenogenesis. Our results indicate a hybrid origin of parthenogenesis in A. trapezoides and shed light on the complex interplay between genomic, microbiome, and reproductive mechanisms in A. trapezoides .

Hidden in the sand: Phylogenomics unravel an unexpected evolutionary history for the desert-adapted vipers of the genus Cerastes - Gabriel Mochales-Riaño; Bernat Burriel-Carranza; Margarida Isabel Barros; Guillermo Velo-Antón; Adrián Talavera; Loukia Spilani; Héctor Tejero-Cicuéndez; Pierre-André Crochet; Alberto Piris; Luis García-Cardenete; Salem Busais; Johannes Els; et al. (Molecular Phylogenetics and Evolution, 2024)